Dampak Bulying Pada Psikologi Anak Usia Dini Dan Progam Pencegahan Pemerintah - Nuri Arifiah Romadhoni; Yes matheos Lasarus Malaikosa; Miftakhul jannah (Pusat Riset dan Inovasi Nasional, 2024)
Bullying is any form of oppression or violence, which is carried out intentionally by a stronger person or group. The purpose of bullying is to hurt other people and is done continuously. This research aims to explore the impact of bullying on individual mental health, especially in children and adolescents. A qualitative approach is used to understand the experiences and perceptions of bullying victims, as well as the psychological and social impacts they have. Through in-depth interviews with bullying victims, parents, teachers and school staff, as well as participatory observation in the school environment, data was collected and analyzed using thematic analysis techniques. Findings show that victims of bullying often experience depression, anxiety, sleep disorders, and feelings of insecurity and protection in the school environment